Anxiolytic and Antidepressant Properties of Alprazolam in Generalized Anxiety Disorder: A Systematic Literature Review - Afira Febriani Surya Wijaya; Hafid Algristian; Ariyani Sri Suwarti (Medicor : Journal of Health Informatics and Health Policy, 2026)
Generalized Anxiety Disorder (GAD) is a highly persistent condition characterized by excessive worry, impaired functioning, and frequent comorbidity with depressive symptoms. Although first-line treatments such as SSRIs and SNRIs are effective, their delayed therapeutic onset and early-treatment anxiogenic effects often lead to poor adherence and treatment discontinuation. This systematic review evaluates the short-term efficacy, safety, and neurobiological mechanisms of alprazolam as a rapid-acting therapeutic option for adults with GAD. Eight studies published between 2011 and 2024—comprising randomized trials, systematic reviews, cohort studies, and neuroimaging investigations—met inclusion criteria. Across clinical trials, alprazolam demonstrated consistent and clinically meaningful reductions in anxiety symptoms within days of initiation, supporting its role as a fast-onset anxiolytic agent. Neurobiological findings showed decreased amygdala hyper reactivity and enhanced prefrontal regulatory activity following alprazolam administration, suggesting mechanisms that align with its rapid clinical effects and potential secondary mood benefits. Adverse events were generally mild, including sedation and psychomotor slowing, and withdrawal symptoms were uncommon when alprazolam was prescribed short-term with supervised tapering. However, the evidence base remains limited by short follow-up periods, small mechanistic samples, and a lack of robust long-term comparative studies. Overall, the findings indicate that alprazolam may serve as a useful short-term adjunct during periods requiring rapid symptom stabilization, particularly when initiating antidepressant therapy. Further research is needed to clarify its long-term safety, functional outcomes, and optimal integration into contemporary treatment pathways.